Innovative Learning Strategies; Analysis of Study Books Using the PAILKEM Approach by Hamzah B. Uno - Istiqomi Nur Aulia (LECTURES: Journal of Islamic and Education Studies, 2022)
This study aims to examine innovative learning strategies; analysis of the study book with the PAILKEM approach by Prof. Dr. Hamzah B. Uno, M.Pd. The type of research used by the author is using a qualitative approach. The qualitative research method is literature study which uses books and literature as the main object related to innovative learning strategies. The conclusion from this study is that the learning strategy is a learning process designed in such a way, structured, and conditioned for students to learn. The relationship between teachers and students becomes a relationship of learning and mutual building. If the application of innovative learning is carried out by the teacher effectively, it can grow and even develop students who have self-creativity. The more creative, the higher the level of stimulation of students, so that it has a positive impact on their learning process. According to Hamzah B. Uno, a teacher must be able to create an atmosphere in such a way that students actively ask questions, question, and also express their ideas. Besides being active, learning should also be fun.